Neutralization of the induced VEGF-A potentiates the therapeutic effect of an anti-VEGFR2 antibody on gastric cancer in vivo - Tetsuo Mashima (Nature Portfolio, 2021)
Abstract The vascular endothelial growth factor (VEGF)/VEGF receptor (VEGFR) axis is an essential regulator of angiogenesis and important therapeutic target in cancer. Ramucirumab is an anti-VEGFR2 monoclonal antibody used for the treatment of several cancers. Increased circulating VEGF-A levels after ramucirumab administration are associated with a worse prognosis, suggesting that excess VEGF-A induced by ramucirumab negatively affects treatment efficacy and that neutralizing VEGF-A may improve treatment outcomes. Here, we evaluated the effect of combination treatment with an anti-VEGFR2 antibody and anti-VEGF-A antibody on gastric tumor progression and normal tissues using a preclinical BALB/c-nu/nu mouse xenograft model. After anti-VEGFR2 antibody treatment in mice, a significant increase in plasma VEGF-A levels was observed, mirroring the clinical response. The elevated VEGF-A was host-derived. Anti-VEGF-A antibody co-administration enhanced the anti-tumor effect of the anti-VEGFR2-antibody without exacerbating the toxicity. Mechanistically, the combination treatment induced intra-tumor molecular changes closely related to angiogenesis inhibition and abolished the gene expression changes specifically induced by anti-VEGFR2 antibody treatment alone. We particularly identified the dual treatment-selective downregulation of ZEB1 expression, which was critical for gastric cancer cell proliferation. These data indicate that the dual blockade of VEGF-A and VEGFR2 is a rational strategy to ensure the anti-tumor effect of angiogenesis-targeting therapy.